MUHAMMADIYAH’S WASATIYAH IN PREVENTING EXTREMISM TROUGH STRENGTHENING ISLAMIC MODERATION, EDUCATION AND COMMUNITY-BASED LEADERSHIP - Yan Adhi Wikarsa; Rahmad Hakim (As-Sulthan Journal of Education, 2026)
This article examines the implementation of Muhammadiyah’s Wasatiyah as a preventive strategy in countering extremism through the strengthening of Islamic moderation, inclusive education, and community-based da‘wah and leadership. Employing a qualitative approach through library research, the study synthesizes classical and contemporary literature to understand wasatiyah as both a normative framework and a practical guide in religious and social life. The findings indicate that wasatiyah is understood as a principle of the middle path that emphasizes justice, balance, and tolerance, while rejecting all forms of ideological and practical extremism. Within the Muhammadiyah context, wasatiyah is institutionalized through the ideological foundations of tajdid, purification, and the orientation of Progressive Islam (Islam Berkemajuan), which are integratively implemented across education, da‘wah, and institutional policies. Muhammadiyah education serves as a strategic arena for internalizing values of moderation through inclusive curricula, character development, and dialogical learning environments. Meanwhile, community-based da‘wah and participatory leadership strengthen social empowerment and community resilience against extremist influences. This study affirms that Muhammadiyah’s Wasatiyah represents a coherent and adaptive model of religious praxis oriented toward social welfare and the sustainability of peace in plural societies.